A coupled sliding and rolling friction model for DEM calibration. (August 2017) - Syed, Zamir; Tekeste, Mehari; White, David
Highlights: Sliding and rolling friction can be combined to form an effective friction coefficient. Effective friction coefficient is correlated with bulk friction. Residual strength of a granular material can be uniquely calibrated using effective friction coefficient. Abstract: The accuracy of dense Discrete Element Method (DEM) simulations is sensitive to initial density, contact orientation, particle size and shape, and interparticle interaction parameters including contact stiffness, cohesion, coefficients of friction, and coefficients of restitution. Although studies have characterized the effects of individual particle interaction parameters on mechanical responses of loaded granular material, research combining DEM parameters for calibration is scarce. Robust DEM calibration methodology combining sliding and rolling friction coefficients was developed and validated to predict bulk residual soil strength of initially dense DEM particle assemblies.